2015
DOI: 10.1002/bjs.9744
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of surgery and outcomes in patients with primary aldosteronism

Abstract: Background: Primary aldosteronism (PA) is the most common cause of secondary hypertension. The main aims of this paper were to review outcome after surgical versus medical treatment of PA and partial versus total adrenalectomy in patients with PA. Cutting edge articles are invited by the BJS Editorial Team, and focus on how current research and innovation will affect future clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
105
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 68 publications
11
105
7
1
Order By: Relevance
“…The differentiation between unilateral and bilateral disease is essential for diagnosis confirmation and proper treatment. Patients with bilateral hyperplasia are treated with a mineralocorticoid receptor antagonist, whereas the subjects with a unilateral adenoma undergo adrenalectomy [8,9]. Because aldosterone-producing microadenomas and multiple bilateral lesions are often undetectable on computed tomography (CT), there is a substantial risk of misdiagnosis when using only CT scanning [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation between unilateral and bilateral disease is essential for diagnosis confirmation and proper treatment. Patients with bilateral hyperplasia are treated with a mineralocorticoid receptor antagonist, whereas the subjects with a unilateral adenoma undergo adrenalectomy [8,9]. Because aldosterone-producing microadenomas and multiple bilateral lesions are often undetectable on computed tomography (CT), there is a substantial risk of misdiagnosis when using only CT scanning [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This limits the usefulness of the results obtained, since it must be noted that patients with bilateral PA are in general less responsive to monotherapy with MRA than those with unilateral PA [17]. Comparisons between surgically and medically treated patients with PA should, therefore, be interpreted with caution [16].…”
Section: Medical Therapy Vs Surgerymentioning
confidence: 97%
“…This limits the usefulness of the results obtained, since it must be noted that patients with bilateral PA are in general less responsive to monotherapy with MRA than those with unilateral PA [17]. Comparisons between surgically and medically treated patients with PA should, therefore, be interpreted with caution [16].The effects on improvement of BP and hypokalemia were similar in surgically and medically treated patients in six studies, and surgery was reported to be superior in another six studies [16]. Of note, in German Conn's registry, the observed all-cause mortality following adrenalectomy was reduced compared with medical treatment [7].…”
mentioning
confidence: 97%
See 2 more Smart Citations